PENGARUH PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PENERIMAAN PAJAK (Analisis Data Tahun 2012-2023) - Agustina, Agustina; Wahyuni, Sri; Asrida, Asrida (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2024)
This research aims to analyze and explain the influence of Economic Growth and the Human Development Index on Tax Revenue during 2012-2023 in Indonesia. Quantitative research using multiple regression methods. The results of this research state that economic growth has a positive effect on tax revenue, and HDI also has a positive effect on tax revenue. The simultaneous contribution of economic growth factors and HDI to tax revenues is 89.8%.